Some issues in education for development: A review of "Education for Development or Underdevelopment?" by M. K. Bacchus (Waterloo, Ontario: Wilfrid Laurier University Press, 1980) - Layne, Anthony (1981)
This review essay identifies four major weaknesses in Bacchus' book: 1) a lack of clarity on exactly what "development" means in the context of the study; 2) inadequate treatment of two factors--the Common Entrance Examination and the private primary schools--which play a vital role in perpetuating social and economic inequality throughout the Commonwealth Caribbean; 3) an unsatisfactory explanation of the rapid growth in secondary school enrolment from the 1960s; and 4) a "dual economy" thesis, which perhaps obscures more than it reveals
Keywords: Education and development